Numerical modelling of rowing blade hydrodynamics - Sliasas, A.; Tullis, S. (Sports Engineering, 2009)
The highly unsteady flow around a rowing blade in motion is examined using a three-dimensional computational fluid dynamics (CFD) model which accounts for the interaction of the blade with the free surface of the water. The model is validated using previous experimental results for quarter-scale blades held stationary near the surface in a water flume. Steady-state drag and lift coefficients from the quarter-scale blade flume simulation are compared to those from a simulation of the more realistic case of a full-scale blade in open water. The model is then modified to accommodate blade motion by simulating the unsteady motion of the rowing shell moving through the water, and the sweep of the oar blade with respect to the shell. Qualitatively, the motion of the free surface around the blade during a stroke shows a realistic agreement with the actual deformation encountered during rowing. Drag and lift coefficients calculated for the blade during a stroke show that the transient hydrodynamic behaviour of the blade in motion differs substantially from the stationary case.